Optimizing renewable energy portfolios with a human development approach by fuzzy interval goal programming - Hashemizadeh, Ali; Ju, Yanbing (Sustainable cities and society, 2021)
•Developing a systematic assessment framework for shaping a RE portfolio.•Considering human development as a primary parameter in RE strategic planning.•Extending the classic FIGP to provide the setting of interval coefficients.•Illustrating the proposed model's capability using a real-world scenario in China. Human development (HD) is considered one of the main metrics for determining the development level of a region. The central motivation of this research is establishing a strategic decision-making paradigm for optimizing renewable energy project (REP) portfolios, with a particular application to east China to quantify how HD influences a REP portfolio selection. The REP portfolio selection is subject to many unclear criteria and various sustainability goals. Fuzzy interval goal programming (FIGP) models are used to deal with the imprecision and uncertainty of the models' goals and coefficients. In this study, firstly, four objectives of social, economic, environmental, and technical criteria, as well as 12 sub-criteria were weighted by fuzzy ANP. Secondly, the potential REPs were assessed on these criteria to deal with the underlying ambiguities. Thirdly, the performance of potential projects was evaluated by the MABAC technique. Fourthly, a mixed-integer linear programming model was constructed and the FIGP is employed to form an optimal portfolio. Eventually, a sensitivity analysis was done to verify the validity of the suggested system. Based on this study's findings, HD is the most significant criterion. These innovative results will assist policymakers in better understanding the role of HD in the REP portfolio selection process.